2023
DOI: 10.3390/ijms24129892
|View full text |Cite
|
Sign up to set email alerts
|

Various Forms of Programmed Cell Death Are Concurrently Activated in the Population of Retinal Ganglion Cells after Ischemia and Reperfusion

Abstract: Retinal ischemia–reperfusion (IR)—which ultimately results in retinal ganglion cell (RGC) death—is a common cause of visual impairment and blindness worldwide. IR results in various types of programmed cell death (PCD), which are of particular importance since they can be prevented by inhibiting the activity of their corresponding signaling cascades. To study the PCD pathways in ischemic RGCs, we used a mouse model of retinal IR and a variety of approaches including RNA-seq analysis, knockout animals, and anim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…Meanwhile, inactivation of this cascade leads to significant RGC survival in NMDA treated retinas. Our data and the results of other investigators indicate that there is significant RGC death in the presence of the Tnf cytokine in vivo and in vitro 8 , 22 24 , 31 , 36 39 . It has also been shown that inhibition of this cytokine leads to significant RGC survival after NMDA treatment 8 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Meanwhile, inactivation of this cascade leads to significant RGC survival in NMDA treated retinas. Our data and the results of other investigators indicate that there is significant RGC death in the presence of the Tnf cytokine in vivo and in vitro 8 , 22 24 , 31 , 36 39 . It has also been shown that inhibition of this cytokine leads to significant RGC survival after NMDA treatment 8 .…”
Section: Discussionsupporting
confidence: 85%
“…To evaluate the significance of these data, we used the oral iron chelator deferiprone (DFP). It has previously been shown that DFP significantly reduces the level of labile iron in the retina, protecting it from many pathologies 26 31 . We expected that lowering labile iron would lead to reduced NMDA excitotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Ischemia-induced RGC degeneration involves multiple complex cell death pathways [7]. It has been reported that proteins involved in necroptosis (Ripk1 and Ripk3) are present in the retina and that the suppression of these proteins prevents necrosis caused by ischemia-reperfusion and increases RGC survival [8].…”
Section: Introductionmentioning
confidence: 99%